2017
DOI: 10.1074/jbc.m116.763656
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Adhesion G Protein-coupled Receptors

Abstract: Members of the adhesion G protein-coupled receptor (aGPCR) family carry an agonistic sequence within their large ectodomains. Peptides derived from this region, called the sequence, can activate the respective receptor. As the conserved core region of the sequence is highly similar between aGPCRs, the agonist specificity of sequence-derived peptides was tested between family members using cell culture-based second messenger assays. peptides derived from aGPCRs of subfamily VI (GPR110/ADGRF1, GPR116/ADGRF5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 31 publications
(50 reference statements)
2
52
0
1
Order By: Relevance
“…Several aGPCRs besides rat LPHN1 and its homologs in C. elegans and Drosophila , including GPR126, GPR133, GPR64, GPR114, GPR56, GPR110, and GPR116, have been reported to be activated by their Stachel peptide, which functions as a tethered agonist ( Demberg et al., 2015 , Demberg et al., 2017 , Kishore et al., 2016 , Liebscher et al., 2014 , Muller et al., 2015 , Scholz et al., 2017 , Stoveken et al., 2015 ) ( Figures 2 A and 2B). Recent studies showed that addition of the synthesized Stachel peptide on full-length receptors in trans activated the receptors ( Liebscher et al., 2014 , Stoveken et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several aGPCRs besides rat LPHN1 and its homologs in C. elegans and Drosophila , including GPR126, GPR133, GPR64, GPR114, GPR56, GPR110, and GPR116, have been reported to be activated by their Stachel peptide, which functions as a tethered agonist ( Demberg et al., 2015 , Demberg et al., 2017 , Kishore et al., 2016 , Liebscher et al., 2014 , Muller et al., 2015 , Scholz et al., 2017 , Stoveken et al., 2015 ) ( Figures 2 A and 2B). Recent studies showed that addition of the synthesized Stachel peptide on full-length receptors in trans activated the receptors ( Liebscher et al., 2014 , Stoveken et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Jedoch ist der Einsatz im endogenen Expressionssystem nicht besonders zielgerichtet, da ho-he Konzentrationen und Lösungsmittelzusatz erforderlich sind. 22) Die aGPCR-Forschung sucht daher nach wie vor nach kleinmolekularen Agonisten und Antagonisten. Breit angelegte Screenings lieferten bereits erste agonistische und antagonistische Substanzen, die jedoch noch nicht rezeptorspezifisch sind.…”
Section: Eigenheiten Der Strukturunclassified
“…GPR116 is also known as Ig-Hepta which has Ig-like repeats in the N-terminal extracellular domain and is highly expressed in the lung [ 64 ]. GPR116 is thought to be an orphan GPCR carrying an agonistic protein sequence ( Stachel sequence) that functions as a tethered agonist after the removal or a structural change of the N-terminal from the C-terminal fragment of the Stachel sequence [ 77 ]. Recently, the activation of the GPR116 by synthetic peptides resembling the C-terminal fragment has been reported [ 77 ].…”
Section: Surfactant Homeostasis In the Alveolar Spacementioning
confidence: 99%
“…GPR116 is thought to be an orphan GPCR carrying an agonistic protein sequence ( Stachel sequence) that functions as a tethered agonist after the removal or a structural change of the N-terminal from the C-terminal fragment of the Stachel sequence [ 77 ]. Recently, the activation of the GPR116 by synthetic peptides resembling the C-terminal fragment has been reported [ 77 ]. In addition, SP-D may function as a ligand activating the GPR116 [ 64 ].…”
Section: Surfactant Homeostasis In the Alveolar Spacementioning
confidence: 99%